ARTISTIC THOUGHT IN THE PROCESS OF GLOBALIZATION AND LOGICAL CONSISTENCY - Nasirov Azimidin Normamatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Nasirov's article "Artistic Thinking and Logical Consistency in the Globalization Process" analyzed the creative processes in the novels of later years, the artistic interpretation of the human concept, and the interpretations , which is a product of the novelistic thinking. In the analysis, poetic interpretation changes, artistic evolution, image, character, and psychologism interpretations in the novel genre were analyzed..